2019
DOI: 10.1097/aog.0000000000003353
|View full text |Cite
|
Sign up to set email alerts
|

Urologic Injury and Fistula After Hysterectomy for Benign Indications

Abstract: OBJECTIVE: To explore the rates and risk factors for sustaining a genitourinary injury during hysterectomy for benign indications. METHODS: In this population-based cohort study, all women who underwent hysterectomy for benign indications were identified from the Office of Statewide Health Planning and Development databases in California (2005–2011). Genitourinary injuries were further classified as identified at the time of hysterectomy, identified aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…It is commonly thought that the risks of surgery are higher when a patient has endometriosis, but this is based on general (and often retrospective) gynecologic surgery literature. For example, the odds ratio of a genitourinary injury during hysterectomy for a benign indication was 1.46 (95% confidence interval 1.36–1.56) when endometriosis was present [ 59 ]. There is less literature on the complication rate amongst those who undergo a combined gynecologic-urologic surgery for endometriosis with a thorough interdisciplinary evaluation, including preoperative imaging.…”
Section: Ureteral Endometriosismentioning
confidence: 99%
“…It is commonly thought that the risks of surgery are higher when a patient has endometriosis, but this is based on general (and often retrospective) gynecologic surgery literature. For example, the odds ratio of a genitourinary injury during hysterectomy for a benign indication was 1.46 (95% confidence interval 1.36–1.56) when endometriosis was present [ 59 ]. There is less literature on the complication rate amongst those who undergo a combined gynecologic-urologic surgery for endometriosis with a thorough interdisciplinary evaluation, including preoperative imaging.…”
Section: Ureteral Endometriosismentioning
confidence: 99%
“…When isolated to only prospective data(21-23) estimated rates of LUTI are 12-28 times higher. Moreover, recent analyses utilizing comprehensive state-wide claims-based analysis suggest that rates of LUTI are likely greater than previously estimated within retrospective data; these contemporary state database analyses report a 1.8% overall LUTI rate and 0.70-0.78% ureteral injury rate (10,24). Based on these estimates, we our model suggests that universal cystoscopy is likely costeffective among all women undergoing laparoscopic hysterectomy.…”
Section: Discussionmentioning
confidence: 63%
“…Our model also encompassed a one-year time horizon, as opposed to 30-day or 90-day outcomes which have been used to inform some prior analyses (3,7,29). Notably, a recent study revealed almost half of repairs for urologic injury from benign hysterectomy occurred outside these windows (median 84 days; IQR 21-274) (24). Third, our model incorporated dynamic estimates of the underlying rate of LUTI and its intraoperative detection by cystoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the odds ratio of a genitourinary injury during hysterectomy for benign indication was 1.46 (95% confidence interval 1.36-1.56) when endometriosis was present. 55 There is less literature on the complication rate amongst those who undergo combined gynecologic-urologic surgery for endometriosis with a thorough interdisciplinary evaluation, including preoperative imaging. It is currently thought the cumulative surgical complication rate for patients surgically treated for UE is estimated to be 9%.…”
Section: Postoperative Complicationsmentioning
confidence: 99%